Indoor Radio Planning : a Practical Guide for GSM, DCS, UMTS, HSPA and LTE. - Tolstrup, Morten (John Wiley & Sons, 2011)
Why is indoor coverage needed, and how it is best implemented? As the challenge of providing higher data speeds and quality for mobile applications intensifies, ensuring adequate in-building and tunnel coverage and capacity is increasingly important. A unique, single-source reference on the theoretical and practical knowledge behind indoor and tunnel radio planning, Indoor Radio Planning, Second Edition provides an overview of mobile networks systems and coverage solutions with GSM, UMTS, HSPA and LTE cellular systems technologies as a backdrop. All of the available solutions, from basic passive.